Penguatan Pencegahan Kekerasan Seksual pada Remaja Putri di Pondok Pesantren melalui Peran Kader Satri Berencana (KARINA) - Permatasari, Elok; Astuti, Nur Fitri Widya; Rizqia, Malika Ayu (UNEJ e-Proceeding, 2023)
Background: Cases of sexual violence against children continue to increase yearly, and East Java province has the highest number of sexual violence cases in Indonesia in 2022. In 2021, KPAI noted that 36% of victims of sexual violence were junior high school / middle school-age children. One of the causes of this condition is the lack of access to information on sexual and reproductive education for adolescents. The limited access of adolescents with parents in the boarding school environment makes adolescent girls spend more of their days in the boarding school environment with their peers, so the role of KARINA is needed to provide information related to reproductive health and sexual violence. KARINA education and strengthening activities aim to improve the skills and confidence of adolescents in their duties as peer educators and counselors. Method: This activity was carried out at MTs Unggulan Nuris Jember Regency from September 5 to 19, 2022. This activity uses the Participatory Action Research method involving KARINA and 59 female students. Result: This activity was carried out through two stages: training for KARINA and providing education by KARINA to 59 peers. Most aspects of knowledge about sexual violence of adolescent girls have increased after the intervention. The majority of young women understand that exhibitionist behavior is sexual violence behavior. However, most young women do not understand who could potentially become a perpetrator of sexual violence. Conclusion: Overall, adolescent girls have gained comprehensive knowledge about reproductive health and the risk of sexual violence. In addition, KARINA has also played a role as a peer educator in increasing adolescent girls' knowledge about sexual violence, contributing to efforts to protect adolescent girls from the risk of sexual violence.Keywords: cadres of santri, peer educator, sexual abuse prevention.